(untitled) - Grant, David (Oxford, 2005)
A two-level foundation course in business English. 100 hours of teaching material, supported by a further 100 hours of self-study materials on CD-ROM, on audio CD, in the Student's Book and Workbook, and on the Business Focus website.
Keywords: English language,English language; Business english,Textbooks for foreign speakers